American State and Local Politics : Direction for the 21st Century - WEBER, Ronald E (Chatham House Pub., 1999)
Ronald E. Weber and Paul Brace bring together a distinguished team of scholars of state and local government to provide an array of viewpoints on the impact of the major institutional changes that have been taking place over the past three decades. These experts discuss the current status of state and local government practices and identify some of the challenges facing officials today.